Reseptor Androgen dan Organ Reproduksi Pria - Zulfitri Zulfitri (Jurnal Kedokteran Syiah Kuala, 2006)
Abstrak.   Hormon  androgen  berperan  penting    dalam   perkembangan   scksual    individu    jaruan.   Mormon   androgen yang  penting  adalah   hormon  testosteron   dan  hormon  dyindrotestosteron.      Ke1j:1  hormon  androgen    pada sel  target diperantarai  oleh   molekul    reseptor   hormon  androgen  yang  dapat   mengikat    hormon  androgen,  mengikat   gen dan mengatur   transkripsi     gen.  Epididimis    merupakan   salah    satu   organ   target   hormon   androgen.    Fungsi   utarna epididimis    rnerupakan  ternpat  pernatangan  spermatozoa.    Fungsi   ini   dapat  dimungkinkan   karna  adanya  aktivitas absorbsi   dan  sekresi    dari  sel-sel    epitel   epididimis.      Aktivitas    tersebut    mernbutuhkan      horrnon  androgen   dan molekul   reseptor  androgen  sebagai  perantara  kerja.   Suatu  ketidak  normalan  dari  reseptor  androgen  atau  bahkan hilangnya  reseptor  androgen  pada sel  target,  menyebabkan   kelainan  yang disebut   sebagai   Androgen  insensitivity Syndrom.(JKS 2006;1:39-48) Kata   Kunci: Reseptor,  Androgen,   Reproduksi,  Pria Abstract.    Androgen   hormones  play  an  important   role   in  male   sexual    development.     There  are  two  important kinds   of androgen  hormones;  they are testosterone   and dyindrotestosteron.     The  work of androgen  hormones  on target   cells is  mediated  by the androgen  hormone  receptor  molecules  that could  bind   the androgen,  binding   and regulating   genes  transcription.   The  epididymis   is  a target  organ  of androgen   hormones.   The  main   function   of epididymis    is  used  as a place  for spermatozoa   maturation.    This  function  may  possibly   be made  since   there are the  absorption   and  secretion   activities     of  the  epididymis    epithelial     cells.  These   activities     require  androgen hormones  and androgen  receptor  molecules  as the mediator.   One of the androgen  receptor  abnormalities  or even the  loss   of  androgen   receptors   on  target  cells   will  create  a  kind  of  disorder   called  androgen   insensitivitysyndrome.  (JKS 2-006;1:39-48) Keywords:Receptors, Androgen, Reproduction,Male